Emergency Remote Teaching Practices During COVID-19 In Malaysia - Siti Hajar Halili (IAHN-TP Palangka Raya, 2022)
The spread of Covid-19 around the world has affected everyone in many different aspects, education is not excluded. One of the distinctive impacts of this pandemic on education is the closure of educational institutions to minimize and avoid further spreading of the virus. This has caused tremendous stress on all educators and students because both parties are left with no choice but to resort to online learning platforms to hold their classes. This shift into virtual classrooms has left them flocking to online learning platforms to resume the learning. Although there are a lot of advantages to remote learning, we must also be aware there are issues that need to be addressed regarding remote learning. The outbreak of Covid-19 has certainly been a tough time for everyone, including educators, students, and policymakers. It is therefore vital to have the right attitude in tackling the problems that arise from the current change in education. When it comes to practices, there are a lot of aspects to cover. The policymakers need to painstakingly come up with options that prioritize both the educators and learners. Educators also need to review their lesson plans and equip themselves with ICT knowledge. The best practice that they can do after the Covid-19 outbreak is they should study more about our education system and change where necessary so that students can catch up with the lesson that they have left behind because of this pandemic.